THE ROLE OF AUTHENTIC MATERIALS IN IMPROVING LISTENING SKILLS FOR B1 LEVEL STUDENTS - Rakhmonova Madina; Erkinova Husniya (Western European Studies, 2024)
Since the demand for learning foreign languages has been increasing dramatically, year by year teachers and academics are making new methods for teaching the foreign languages easily. While learning any language including English, every academic pay attention to each aspects of the language (grammar, vocabulary, listening, reading). Moreover, this paper investigates the efficiency of utilizing authentic materials to enhance the listening skills of B1 level students. With an increasing emphasis on communicative competence, the role of authentic materials in language teaching has gained significant attention. This study explores the impact of integrating authentic materials, such as podcasts, news clips, and videos, into listening activities designed for B1 level learners. Drawing on principles of task-based learning and authentic learning experiences, the study examines the effectiveness of authentic materials in engaging students and fostering meaningful listening comprehension.
Keywords: authentic materials; teaching foreign languages; innovative approaches